9. CLINICAL CHARACTERISTICS OF PATIENTS WITH CLOSED FEMUR FRACTURES OPERATED AT VIET DUC UNIVESITY HOSPITAL (Vietnam Journal of Community Medicine, 2023)
Objective: Describe some clinical characteristics of patients undergoing femur fracture surgery at Viet Duc Hospital.Subject and method: A cross-sectional descriptive study on 150 patients undergoing femur fracture surgery at Viet Duc Univesity Hospital.Results: The patient’s pain level gradually decreased with time after surgery. The rate of patients with fever on the first day after surgery was 6.7%; this rate on the 2nd and 5th day after surgery was 3.3% and 0.7%. The rate of patients with hypotension on the first day after surgery was 2.0%. The percentage of patients with pale skin and mucous membranes before surgery was 14.7%; The first day after surgery was 16.7%, the rate on the 2nd day after surgery was 6.0% and the 5th day after surgery was 0.7%. On the first day after surgery, the rate of patients with incisions that secreted much fluid was 32.0%; this rate decreased to 8.7% on day 2 and 2.0% on day 5 after surgery. The rate of patients with insomnia gradually decreased over time after surgery.Conclusion: Clinical symptoms of the patient decreased with time after surgery.
Keywords: Clinical symptoms, femur fracture surgery.